Dissemination of health check application for kindergarten students in education and monitoring of student health - Evina Widianawati; Widya Ratna Wulan; Ika Pantiawati; Fitria Wulandari (Community Empowerment, 2022)
Every month, Ustman Bin Affan Islamic School Kindergarten manually records students' weight, height, and dental health. In addition, students do not yet understand the importance of keeping themselves clean after playing. The purpose of this program is to socialize the use of the student health check application for monitoring and educating students' health so they can maintain their health during a pandemic. During four sessions, socialization of the use of the kindergarten children' health check application, education on health protocols, and education on dental health and balanced nutrition was carried out. According to the program's results, teachers now have a 135% greater understanding of how to use the application. Based on the FGDs, students understood the application of health protocols, were able to take care of their teeth to prevent damage and had a balanced nutritional diet. All students dared to come forward to re-practice the steps of washing hands, brushing their teeth and choosing a balanced nutritional diet.